Deconstructive principles of Jacques Derrida - Behairi, Hanadi Muhammad (Journal of Arabic Language Sciences and Literature, 2023)
First introduced by Jacques Derrida (1930-2004), the concept of deconstruction is a theory and form of criticism that seeks to reconstruct a text to produce a creative text that comprises the same components in a different manner; a more attractive, impactful manner from the reader’s point of view. Impact measurement became one of the main factors in the measurements of creative elements in the construction process. However, impact varies given the disparity of cultural legacy among communities who speak the same language with different accents, and certainly, among communities who speak different languages.What is the strategy of reconstructing the text after deconstructing it, and how do the mind and heart contribute to the impact of text reconstruction? Is deconstruction one of the concepts that can be regarded humanly despite the difference in languages? In other words, can one resort to shared human values to understand the text strategy, such as the values of laughter and crying, which express feelings that are almost universally agreed upon? Can globalization unite viewpoints in assessing the value of deconstruction as one of the internal criticism theories and approaches used to understand and interpret the genius of a text and give value to the recipient in deconstructing the text and rebuilding its metaphors professionally? How to understand Jacques Derrida's insistence on the utility of deconstruction and its unique ability to interpret the genius of a text and achieve pragmatic value? This paper will try to find answers to all these questions in line with the dialectic of languages in deconstructive rhetoric.
Keywords: literary criticism; deconstructive rhetoric; Jacques Derrida